Tonic pain reduces autonomic responses and EEG functional connectivity elicited by affective stimuli. (6th February 2022) - Alba, Guzmán; Vila, Jaime; Miranda, José G. V.; Montoya, Pedro; Muñoz, Miguel A.
Abstract: Most pain studies have focused on only two aspects of pain: the influence of pain on attentional processing and the modulation of pain perception by affective stimuli. However, the influence of tonic pain on the attentional processing of affective stimuli has not been studied. In this study, we investigated the effects of tonic pain on the attentional processing of affective stimuli, focusing on autonomic responses and their relationship with both EEG power and functional connectivity. Forty participants (20 men and 20 women) received tonically painful and nonpainful thermal stimulation while viewing blocks of pleasant, unpleasant, or neutral images. The galvanic skin conductance response (SCR), electrocardiographic activity, and electroencephalographic (EEG) activity in the delta and theta bands were recorded. Participants rated the unpleasantness of the pain at the end of each block. Typical affective SCR and heart rate (HR) patterns were found in the no‐pain condition, but when the pain was delivered, these patterns disappeared. EEG power and functional connectivity results showed that tonic pain affected the delta band in the central region during pleasant and unpleasant image blocks. Our findings suggest that tonic pain captured attentional focus and reduced the cognitive resources available for processing affective stimuli, altering the emotional experience associated with pain. Abstract : Previous studies with pain patients suggest that pain reduces the attentional processing of affective stimuli. However, these results could be a consequence of affective disorders related to pain diseases. The current article provides new subjective and physiological evidence that tonic pain reduces the attentional processing of affective stimuli in healthy participants.